Pseudomonas fluorescens Filamentous Hemagglutinin, an Iron-Regulated Protein, Is an Important Virulence Factor that Modulates Bacterial Pathogenicity - Sun, Yuan-Yuan; Chi, Heng; Sun, Li (Frontiers in Microbiology, 2016)
Pseudomonas fluorescens is a common bacterial pathogen to a wide range of aquaculture animals including various species of fish. In this study, we employed proteomic analysis and identified filamentous hemagglutinin (FHA) as an iron-responsive protein secreted by TSS, a pathogenic P. fluorescens isolate. In vitro study showed that compared to the wild type, the fha mutant TSSfha (i) exhibited a largely similar vegetative growth profile but significantly retarded in the ability of biofilm growth and producing extracellular matrix, (ii) displayed no apparent flagella and motility, (iii) was defective in the attachment to host cells and unable to form self-aggregation, (iv) displayed markedly reduced capacity of hemagglutination and surviving in host serum. In vivo infection analysis revealed that TSSfha was significantly attenuated in the ability of dissemination in fish tissues and inducing host mortality, and that antibody blocking of the natural FHA produced by the wild type TSS impaired the infectivity of the pathogen. Furthermore, when introduced into turbot as a subunit vaccine, recombinant FHA elicited a significant protection against lethal TSS challenge. Taken together, these results indicate for the first time that P. fluorescens FHA is a key virulence factor essential to multiple biological processes associated with pathogenicity.